Kontribusi Optimisme Dan Dukungan Sosial Terhadap Resiliensi Mengerjakan Skripsi Mahasiswa Ilmu Pendidikan - Andriyanto, Aurelia Andriyaniputri; Jamain, Ririanti Rachmayanie; Permatasari, Nina (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
The problem in this research is how to contribute each variable to the resilience of working and whether the two variables of optimism and social support together will contribute to the resilience of working on the thesis. This study aims to analyze the contribution of optimism and social support to the resilience of working on a thesis for the 2016-2017 Faculty of Educational Sciences Students, FKIP ULM. This study uses a quantitative approach with the type of contribution research. The data collection tool uses a questionnaire with a purposive random sampling technique. This research was conducted on students of the Department of Education, FKIP ULM, Class of 2016-2017. The population in this study found 1,307 people, and a sample was obtained using an error rate of 1%, namely 440 students. The data analysis technique used descriptive statistics, simple linear regression, and multiple linear regression. The results showed that there was a positive and significant effect; this means that there is a positive influence made by optimism and social support on the resilience of working on the thesis can be given in this study and so it is possible, valid, and generalized to the population of optimism and social support for resilience. working on a thesis for students of the Department of Education, FKIP ULM. The contribution of optimism and social support to the resilience of doing the thesis is 8.2%.